Complex genetic architecture of three‐dimensional craniofacial shape variation in domestic pigeons. Issue 6 (16th December 2021) - Boer, Elena F.; Maclary, Emily T.; Shapiro, Michael D.
Abstract: Deciphering the genetic basis of vertebrate craniofacial variation is a longstanding biological problem with broad implications in evolution, development, and human pathology. One of the most stunning examples of craniofacial diversification is the adaptive radiation of birds, in which the beak serves essential roles in virtually every aspect of their life histories. The domestic pigeon ( Columba livia ) provides an exceptional opportunity to study the genetic underpinnings of craniofacial variation because of its unique balance of experimental accessibility and extraordinary phenotypic diversity within a single species. We used traditional and geometric morphometrics to quantify craniofacial variation in an F2 laboratory cross derived from the straight‐beaked Pomeranian Pouter and curved‐beak Scandaroon pigeon breeds. Using a combination of genome‐wide quantitative trait locus scans and multi‐locus modeling, we identified a set of genetic loci associated with complex shape variation in the craniofacial skeleton, including beak shape, braincase shape, and mandible shape. Some of these loci control coordinated changes between different structures, while others explain variation in the size and shape of specific skull and jaw regions. We find that in domestic pigeons, a complex blend of both independent and coupled genetic effects underlie three‐dimensional craniofacial morphology. Abstract : Research Highlights: Birds represent one of the most striking examples of skull and jaw diversification among vertebrates. The exceptional diversity of skull and jaw shapes within domestic pigeons provides an outstanding opportunity to study the genetic architecture of vertebrate craniofacial morphology. We used a combination of geometric morphometrics and quantitative trait loci (QTL) mapping to measure skull and jaw shape variation in domestic pigeons and identified a set of genetic loci associated with 3D shape variation, including beak curvature. Our results provide evidence for a complex genetic basis for skull and jaw shape in pigeons.